Malignant pleural mesothelioma: main topics of American Society of Clinical Oncology clinical practice guidelines for diagnosis and treatment - Szolkowska, Malgorzata; Blasinska-Przerwa, Katarzyna; Knetki-Wroblewska, Magdalena; Rudzinski, Piotr; Langfort, Renata (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Malignant pleural mesothelioma (MPM) is a rare, asbestos-related neoplasm with a poor prognosis. Men are more often affected than women and the incidence in males in the US is 1.5/100,000/year (according to data in the SEER database), in Turkey it is 2.88/100,000/year and in Great Britain it is 5.4/100,000/year (1,2).